Development of magnetic current imaging for the failure analysis of 3D package technology - Kor, Katherine Hwee Boon. (2013)
“More than Moore” trend has triggered the development of three-dimensional (3D) technologies which are important in terms of their reliability and performance. However, the introduction of these new technologies presents new challenges in fault isolation and failure analysis of short circuits, open circuits or intermittent failures. Magnetic current imaging (MCI) and 3D X-Ray computed tomography (CT) are some of the more advanced and non-destructive techniques which may be able to overcome the challenges.